Innovative Activity in the Industry of Ukraine: Problems, Risks, and Directions of Stepping Up - Pidorycheva, I.Yu. (Science and Innovation, 2024)
The general status and recent positive trends in the innovative activities of enterprises in Ukraine have been discussed. The key challenges and discouraging factors affecting the interest of Ukrainian corporations in innovations have been analyzed. The risks of sustainability of the existing trends in the sphere of innovative and technological development, which can lead to the preservation of outdated structure of the national economy have been identified. The priorities and mediumterm measures for overcoming the existing barriers in implementing a new model of economic development based on investments into innovative activities, new industrialization, and industrial recovery have been offered.